G191 Paediatric free open access medical education (FOAM) – behaviours, trends and implications. (25th October 2020) - Barton, J; Round, J; Knight, K
Abstract : Introduction/Aims: Free Open Access Meducation (FOAM) is a movement built around freely available (mostly online) medical education resources. Over the past decade its popularity has increased exponentially, to begin with primarily in critical care and emergency medicine, but more recently in paediatrics. However, little is known about FOAM users or their behaviours. This study aimed to investigate the user behaviours of one of the most popular paediatric FOAM websites. Methods: Using Google analytics for the website we explored user demographics and their patterns of behaviour. Descriptive statistics were used to identify early trends and highlight areas of potential future research. Results: 5, 583 sessions were logged over four months in 2018/19. Users came from 146 countries, although the site is primarily written and promoted in the UK. 68.9% of users were female; most were 25–34 years; 57.3% used a mobile device, the remainder using desktop and tablet devices. Those using mobile devices spent less time using the website and were less likely to access the website via the homepage, instead landing on an article directed by an internet search. Fewer sessions were logged during the weekends than on weekdays. Discussion: FOAM is a rapidly developing form of medical education, demonstrated by large user numbers accessing this site which is just 2 years old. The site is being used by many beyond its intended readership and primarily being accessed from search engines. The behaviours of users suggest potential motivating factors for use, such as the need for timely, succinct information. Google Analytics has the ability to provide rich and meaningful data. To date, the understanding of FOAM as a learning aid has not kept pace with its increasing popularity, we hope that this study encourages others to share their readily available data and contribute to our understanding. Conclusions: Google analytics can powerfully explore FOAM usage. Site curators should develop materials suitable for mobile or desktop usage, mindful also that their readership may well not be healthcare professionals. Given its popularity, further evaluation of user motivations and the effectiveness of FOAM should be prioritised.